ChemInform Abstract: Five‐Membered 2, 3‐Dioxo Heterocycles. Part 92. Reaction of 3‐Aroyl‐1H‐pyrrolo[2, 1‐c][1, 4]benzoxazine‐1, 2, 4‐triones with Ethyl (2Z)‐(3, 3‐Dimethyl‐8‐oxo‐2‐azaspiro [4.5]deca‐6, 9‐dien‐1‐ylidene)ethanoate. Synthesis of Bridged Analogues of Pyrrolizidine Alkaloids. Issue 36 (15th August 2013) - Konovalova, V. V.; Stryapunina, O. G.; Shklyaev, Yu. V.; Slepukhin, P. A.; Maslivets, A. N.
Abstract Derivatives (III) can be regarded as bridged analogs of pyrrolizidine alkaloids, which exhibit important pharmacological properties.